1992
DOI: 10.1136/jcp.45.9.815
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sentinel and Bactec blood culture systems.

Abstract: Aims: To evaluate the Sentinel automated blood culture system and to compare its performance with that of Bactec. Methods: The Sentinel blood culture system was evaluated in three centres. The performance ofthe system was assessed in comparison with the routine blood culture method used in these centres, the Bactec system. Results: Blood culture sets (n = 2180) consisting of Sentinel aerobic and anaerobic, and Bactec aerobic and anaerobic bottles yielded 218 (10%) clinicaily important isolates. One hundred and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…The culture bottles of the Sentinel blood‐culture system (Difco Laboratories Ltd, East Molesey, Surrey, UK) contain gold‐plated and aluminum alloy electrodes. The system detects microbial growth by measuring relative changes in voltage produced in the media [100]. The future of these four systems remains uncertain, and to our knowledge, large‐scale clinical trials have not yet been communicated.…”
Section: Automated Systemsmentioning
confidence: 99%
“…The culture bottles of the Sentinel blood‐culture system (Difco Laboratories Ltd, East Molesey, Surrey, UK) contain gold‐plated and aluminum alloy electrodes. The system detects microbial growth by measuring relative changes in voltage produced in the media [100]. The future of these four systems remains uncertain, and to our knowledge, large‐scale clinical trials have not yet been communicated.…”
Section: Automated Systemsmentioning
confidence: 99%
“…3,15,17,41 We recognize that the success rate is variable, as it depends mainly on the volume of sample used; currently the positivity rate of TBC in infants is not more than 50% at the best centers. 10,[13][14][15][16][17]20,41 Our rate of positivity is significantly higher than that found by Lee et al, who reported 9.89% positivity in 192 samples obtained from infants with nosocomial sepsis, and that reported by Guerti et al, 15% of 2916 cultures from 1828 neonates, and is lower than the 63% rate reported by Macharashvili et al 19,42,43 The sensitivity and specificity of buffy coat culture (86% and 87%, respectively) are similar to those reported for TBC, which has been reported to have a sensitivity of 30-80% and specificity of 70-100%. These values are modified when more than one blood culture sample is obtained, and also depends on several factors, such as the inoculated volume, the amount of bacteria present in the sample, the incubation time, the sensitivity of the automated system, and the type of organism isolated, as some do not grow on conventional culture media and there is no single culture medium that is suitable to enhance the recovery of all microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] Performance is also influenced by the volume of blood used, the culture media, and the manufacturer. [16][17][18][19][20][21] Separation and staining of the leukocyte-rich layer of a blood sample, also known as the 'buffy coat', 22,23 which contains mononuclear cells and granulocytes, has been used as an alternative tool for the identification of microorganisms, especially in the diagnosis of tropical diseases. 24 However confidence in its use as a diagnostic tool for sepsis has not yet been attained because of its low sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%
“…Neste estudo, foi utilizado o sistema Bactec 9240 ® , que é o mais recente sistema automatizado disponível. Esse sistema tem demonstrado resultados favoráveis, quando comparado a outros 40,41 , além de apresentar todas as vantagens de um siste-ma automatizado: servir ao mesmo tempo como incubador, agitador e sistema de detecção; apresentar tempo menor de detecção de positividade das hemoculturas; propiciar resultados mais confiáveis pela ausência de manipulação após a incubação e pela monitoração contínua, e capacidade de acomodar grande quantidade de frascos [41][42][43][44] .…”
Section: Discussionunclassified